PEMBELAJARAN PENDIDIKAN ISLAM TERHADAP KESETARAAN GENDER - Fauziah, Tiara Dilla; Purwidianto (LPPM STAI Muhammadiyah Probolinggo, 2024)
Gender equality itself does not mean that women's position must be higher than men, but the equality of both, of course, in terms of education. Because by improving the quality of education for women, we will give birth to a generation of intelligent children who will later advance the country in all areas of life. But in reality there is discrimination in the field of education and women are in second place. This research uses a literature study or known as library reserch. Data collection is carried out by collecting and retrieving relevant data then reviewing library sources such as books or journals. The type of research used is qualitative. While the approach used is content analysis, this is done by reviewing the content and explaining the material that has been studied descriptively. These steps are a way to obtain an explanation of Islamic education learning on gender equality. The results of this study show that gender equality in education must be realized, because it can have a good impact on the pace of the world and for students in it. By prioritizing gender equality in the world of education, male students will not feel themselves superior to women in taking part in this field.